Empowering the implementation of different pedagogy in the teaching of faith: Memperkasakan pelaksanaan pedagogi terbeza dalam pengajaran akidah - Abdul, Zuraidah; Zulkifli, Hafizhah; Mahamod, Zamri (Jurnal Pendidikan Bitara UPSI, 2023)
Efforts have been made to ensure that all students receive the best education possible. However, today the issue of student disengagement in learning is still a major issue discussed in the world of education. Thus, a more flexible teaching approach has been introduced, namely differentiated pedagogy which is one of the contemporary teaching approaches implemented in 21st Century Learning aimed at addressing the issue of student diversity. Through this teacher’s approach will customize several aspects of teaching i.e. content, process, outcomes and learning environment so that no student is left behind. Thus, this concept paper discusses the concept and implementation steps of differentiated pedagogy with a focus on teaching Akidah in primary schools. In addition, the challenges of implementing this approach in teaching and its implications for teachers, students, schools, JPNs and teacher training institutes are discussed. The writing of this concept paper will benefit all parties in educational institutions especially in ensuring that all members of the teaching community practice effective teaching approaches while always improving teaching practices that celebrate the diversity of students.